IADC/SPE Drilling Conference 1998
DOI: 10.2118/39391-ms
|View full text |Cite
|
Sign up to set email alerts
|

Friction Analysis for Long-Reach Wells

Abstract: Presently wells are drilled in the North Sea approaching a horizontal reach of 8 km. Plans for the near future is to extend these towards and beyond 12 km. Well friction is one of the most important limiting factors in this process. Torque and drag prognosis are today developed on in-house simulators. Although a good tool for planning, improvements are made on an trial and error basis, and, these simulators have limited availability. To provide more insight into the frictional aspect, a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The aim of deviated well drilling as shown in Fig. 1 is to keep a well in a reservoir for a longer distance and maximise its productivity (Aadnoy and Andersen, 1998). One of the major challenges of deviated well drilling is to manage the mechanical loads on the drill-strings, namely, the so-called axial load transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of deviated well drilling as shown in Fig. 1 is to keep a well in a reservoir for a longer distance and maximise its productivity (Aadnoy and Andersen, 1998). One of the major challenges of deviated well drilling is to manage the mechanical loads on the drill-strings, namely, the so-called axial load transfer.…”
Section: Introductionmentioning
confidence: 99%
“…From the results of the case studies, trajectory controls by use of the minimum-energy method are shown to yield a smooth well path. A smooth well path, meaning less local dogleg severity and microtortuosity, helps reduce wellbore friction (Aadnoy and Andersen 1998;Gaynor et al 2002;McCormick and Wilcox 2013;Menand 2013). Wellbore friction is a limiting factor of the depth of horizontal drilling.…”
Section: Discussionmentioning
confidence: 99%
“…Drilling automation is becoming more commonplace in the oil and gas industry, although the adoption process has fallen behind other industries for many years (Dupre 2013). One of the mostimportant elements of drilling automation is wellbore-trajectory control, especially in the era of extended-reach and horizontal drilling.…”
Section: Introductionmentioning
confidence: 99%
“…6 While the reduction in OD paid benefits in reduced torque, the 4 ¼-inch ID helped to reduce the hydraulic losses through the pipe. This tool joint brought several major benefits to the design.…”
Section: A-6 Planningmentioning
confidence: 99%